Fatty acids, triacylglycerols, and thermal behaviour of various mango (Mangifera indica L.) kernel fats. (February 2019) - Lieb, Veronika M.; Schuster, Laura K.; Kronmüller, Amrei; Schmarr, Hans-Georg; Carle, Reinhold; Steingass, Christof B.
Abstract: Mango processing generates high amounts of unexploited kernels. Lipid profiles and thermal behaviour of kernel fats from seven Mangifera indica L. cultivars originating from Latin America and Thailand were characterised. Total lipid contents ranged between 5.4 and 11.9%. Detailed GC-FID, GC‐MS, and HPLC-DAD-ESI-MS n analyses revealed two fatty acids and five triacylglycerols as novel mango kernel constituents. Owing to the prevailing saturated fatty acids and triacylglycerols, 'Maha Chanook' fat had a significantly higher melting point, the highest solid fat indices at all temperatures, and densely packed crystals as shown by DSC and light microscopy, respectively. In contrast, 'Falan' exhibited high proportions of polyunsaturated fatty acids and triacylglycerols with low equivalent carbon numbers (40–46), resulting in lower melting and crystallisation temperatures and a loosened crystal network. 'Keitt' and 'Palmer' fats showed high proportions of triacylglycerols with medium equivalent carbon numbers (44–52). Mango kernels represent a sustainable source for liquid to semi-solid edible fats suitable for numerous potential applications, e.g., in food and cosmetics. Graphical abstract: Unlabelled Image Highlights: Fatty acid and triacylglycerol compositions of seven mango kernel fats were determined. Lipid composition correlated to geographical provenances of mango kernels. Differing thermal properties and crystal morphologies of the fats were revealed. Mango kernels represent a source of edible fats covering a wide range of potential applications.